Guidelines for Ultrasound in the Radiology Department During the COVID-19 Pandemic. Issue 3 (September 2020) - Sheth, Sheila; Fetzer, David; Frates, Mary; Needleman, Laurence; Middleton, William; Jones, Jill; Podrasky, Ann; Mankowski Gettle, Lori
Abstract : Abstract: The coronavirus disease 2019 is caused by the severe acute respiratory syndrome coronavirus 2. The virus can be spread by close person-to-person contact primarily by respiratory droplets. Given the close proximity of the sonographer or sonologist with the patient during ultrasound examinations, special precautions should be taken to limit the exposure of radiology personnel to patients with coronavirus disease 2019 while still providing optimal patient care. Methods covered in this article include modified workflow, close scrutiny and prioritization of imaging orders, and design of targeted ultrasound protocols. These guidelines summarize the personal experience and insight of multiple colleagues who lead ultrasound sections or are experts in the field. Abstract : Supplemental digital content is available in the text.